Effect of Self Curing Agent on the Properties and Durability of Normal and ‎High Strength Self-Compacted Concrete Properties - Mohammed A. Arab‎, Metwaly A. Abdel-Aziz‎, Fatma R. Mahmoud‎ (International Journal of Advanced Science and Technology, 2020)
Considering the promising performance of Self-compacting concrete, it has been widely used in numerous ‎constructions. Self-curing concrete provides a solution for an enormous saving of water. This research is devoted to ‎evaluating the effect of using different self-curing agents which are polyethylene glycol with molecular weights ‎‎400, 600, 4000, and 6000, and polyacrylamide on the properties of the normal and high strength self-‎compacted concrete samples. Evaluating the results of the flowability, passing-ability, compressive strength, indirect tensile ‎strength, and flexural strength tests is introduced. Results show that increasing of self-curing agent ‎content decreases the slump flow and passing-ability. The optimum dosage of self-curing agents is 0.3% for ‎polyacrylamide, 0.5% for PEG400, PEG600 and PEG6000 and 1.0% for PEG4000. Compressive strength test results till 365 ‎days age shows that adding self-curing agent affect strength positively with age increasing. Specimens containing the ‎optimum dosage of self-curing agents show lower sorptivity than control mixes.‎